2004
DOI: 10.1073/pnas.0400751101
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell expression of the AML1/ETO fusion protein induces a myeloproliferative disorder in mice

Abstract: The t(8;21)(q22;q22) translocation, present in 10 -15% of acute myeloid leukemia (AML) cases, generates the AML1͞ETO fusion protein.To study the role of AML1͞ETO in the pathogenesis of AML, we used the Ly6A locus that encodes the well characterized hematopoietic stem cell marker, Sca1, to target expression of AML1͞ETO to the hematopoietic stem cell compartment in mice. Whereas germ-line expression of AML1͞ETO from the AML1 promoter results in embryonic lethality, heterozygous Sca1 ؉/AML1-ETO ires EGFP (abbrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 46 publications
6
65
0
Order By: Relevance
“…These data unveil an important biological function of AE, and demonstrate that AE can activate PTK signal for cell proliferation by itself and may thus contribute to disease progression. Therefore, these data seem also to be in agreement with the ability of AE alone in inducing myeloproliferative disorder in mouse when appropriate promoter was used to drive the gene expression (14). In exploring the possible mechanism underlying AE-induced up-regulation of C-KIT, we found in U937-A͞E cells that TGF-␤1, a potent negative regulator of hematopoiesis, was down-regulated only 6 h after specific induction of AE.…”
Section: Discussionsupporting
confidence: 70%
“…These data unveil an important biological function of AE, and demonstrate that AE can activate PTK signal for cell proliferation by itself and may thus contribute to disease progression. Therefore, these data seem also to be in agreement with the ability of AE alone in inducing myeloproliferative disorder in mouse when appropriate promoter was used to drive the gene expression (14). In exploring the possible mechanism underlying AE-induced up-regulation of C-KIT, we found in U937-A͞E cells that TGF-␤1, a potent negative regulator of hematopoiesis, was down-regulated only 6 h after specific induction of AE.…”
Section: Discussionsupporting
confidence: 70%
“…This suggested that these fusion proteins are dominant-negative inhibitors of corresponding normal gene function during primitive haematopoietic lineage commitment. In only one exception, where AML-ETO was targeted to the stem cell compartment by Ly6A locus (Fenske et al, 2004) did animals survive and developed a long (>6 months) latency myeloproliferative disease, reinforcing the idea that disease phenotype is dependent of the cellular compartment-targeted and accumulation of mutations.…”
Section: Knock-in Modelsmentioning
confidence: 90%
“…As mentioned in the techniques section, in this approach the mutated exogenous cDNA is targeted in-frame directly to a pre-defined locus by homologous recombination in the ES cells and employed in developing knock-in models of the following: AML1-ETO t(8;21) (Yergeau et al, 1997;Okuda et al, 1998;Fenske et al, 2004), PLZF-RARa t(11;17) (He et al, 1999), CBFb-MYH11 inv(16) t(16;16) found in AML subtype FAB M4Eo (that is myelomonocytic differentiation together with increased eosinophilic progenitors) (Castilla et al, 1996), CBFb-GFP (Kundu et al, 2002), MLL-AF9 t(9;11) found in AML FAB M5 (that is myelomonocytic variants) (Dobson et al, 1999) and MLL-lacZ (Dobson et al, 2000). Resultant AML-ETO or CBFb-MYH11 knock-in fusion genes resulted in embryonic lethality owing to lack of definitive embryonic haematopoiesis in a manner remarkably similar to that of the corresponding (AML1 À/À , CBFb À/À ) knockout animals.…”
Section: Knock-in Modelsmentioning
confidence: 99%
“…Correspondingly, transfection of AML1-ETO into primary human CD34 + hematopoietic progenitors efficiently blocked erythroid lineage commitment, normally denoted by CD36 and GPA upregulation coupled with CD34 and CD13 downregulation [3]. This effect of AML1-ETO was reminiscent of the erythroid blockade uniquely associated with t(8;21)-positive human AMLs and of the erythroid inhibition seen in several murine models of AML1-ETO transformation [51][52][53][54]. AML1-ETO employed a novel mechanism in its inhibition of erythropoiesis, interfering with the acetylation of GATA-1 mediated by p300/CBP.…”
Section: Launchingmentioning
confidence: 99%